The Design and Development of M-CLINIC Apps Mobile Applications - Habsah Mohamad Sabli; Mohammad Fardillah bin Wahi; Valerie Lungan Andrew Nyipa; Celybia Chu Wei Jyi; Mckoy Akam Anak Fabian Umin (International Journal of Advanced Research in Social Studies, 2022)
During the Covid-19 epidemic, health facilities were important to students, however, the government hospitals and clinics were located in the city centre away from PMU and UITM Mukah. Added with the movement control order (MCO), only 80% of staff on duty, this makes it students hard to contact the medical officer and fail to get proper treatment. In PMU and UITM students are allowed to return to the campus with some restrictions and procedures to follow. Hence the purpose of the innovations of M Clinicc Apps in mobile applications is to be created especially for students to make an appointment at Politeknik Mukah (PMU) and Uitm Campus’s clinic or clinics located in Mukah Sarawak, Malaysia. Secondly to determine the level of applications among both institutions using the M Clinic Apps and the purpose of the recommendations. A total of 125 students participates in this study, which also used descriptive statistics. Overall, the students agreed the Clinic Apps were useful during Covid 19 pandemic. In addition, this mobile application innovation project also has a benefit for both institutions because this application can improve the level of management in medical and health services. The management of medical and health services at both institutions needs to be improved because the health of students was important that needs to be taken into consideration, moreover our country is still in a phase where the covid-19 pandemic has not been over yet. Lastly, the health of these students has become the responsibility and priority of the management of PMU and UITM Mukah campus because these students are not under the care of their parents after returning to campus.